Determination of the Biochemical Activity of N-Acetyltransferase Enzyme, NAT2 Gene Production in Children with Environmental Pathology Following Received Treatment - N.R. Kech (Zaslavsky O.Yu., 2016)
The study of the biochemical activity of the enzyme N-acetyltransferase, NAT2 gene production in children from ecologically unfavorable regions (EUR) is extremely important to identify predisposition to environmental pathology, including thyroid, renal and urinary diseases, in a contaminated environment. An example of this region is chemically contaminated Halytskyi, Dolynskyi and Kaluskyi districts and radiologically contaminated Sniatyn district of the Ivano-Frankivsk region. We have examined 239 children from EUR and 70 children from the control group. Age of children - 3 to 18 years, sex: boys - 48 %, girls - 52 %. All children were examined clinically, they underwent instrumental (ultrasound investigation, ultrasound densitometry) and laboratory diagnosis before and after therapy. Using biochemical method, we have determined the activity of N-acetyltransferase enzyme. Low activity of the enzyme encoded by the gene NAT2, in children with environmental pathology causes their low capacity for acetylation, which is the basis for the formation of environment-related diseases of the thyroid gland, bones and kidneys in these children. Membrane-protective, antioxidant, sorption therapy and the use of calcium supplements have a pronounced positive effect on the activity of the enzyme N-acetyltransferase in the blood of the children.